YORUBA POETRY. Published by the Ministry of Education, Ibadan, Nigeria (International Library of African Music, 1959)
pages: 93-95
Keywords: Poetry; Yoruba (African people); African Music; Nigeria; Yoruba Art; Yoruba Poetry